(untitled) (Medico Legal Update, 2020)
In the Republic of Indonesia’s Constitution, Article 22E paragraph (1), it is stated that the execution of the general election must be done in a manner which is direct, general, libre, confidential, honest and fair. Every citizen has a right which is guaranteed constitutionally to participate in the general election including those who are mentally disabled. They have the right to freely participate both directly or by electing the representatives who will be in the government. Historically, the prohibition of the voting rights for mentally disabled people is not in accordance with the Human Rights except with clear circumsance.